ANALISA KAPASITAS DAN KINERJA RUAS JALAN PERINTIS KEMERDEKAAN PONTIANAK - Almaut, Edo Novaldi; AS, Syafaruddin; Kadarini, Siti Nurlaily (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
This paper presents the results of the research performance roads perintis kemerdekaan Pontianak that in terms of the volume of traffic flow, the capacity and the degree of saturation.Calculation analysis and planning in this research using methods MKJI 1997 .The withdrawal of the primary data in the form of geometric figure the road, the volume of traffic, obstacles aside , and speed obtained directly in the location of research, while secondary data obtained from the Badan Pusat Statistik (BPS) and the Dinas Pekerjaan Umum in the form of the population data and the site planÂ  research sites. Based on the results of research on perintis kemerdekaan roads in Pontianak by using the MKJI 1997 obtained volume the top daily an average of 2722 smp/hours in segments 1 and 2712 in segments 2, with capacity of roads 3107.6 smp / hours. The degree of saturation (DS) as much as 0,875 in segments 1 and 0,872 in segments 2 with level of service category "E" on both segments. The results of the projection in the year 2021 showed the value of a larger DS, 1.33 on segments 1 and 2 with a level of service on "F". For it conducted an analysis that are supposed to be improving the performance of Perintis Kemerdekaan in 2021 with change of geometric designs to four lanes undivided two way 2 (4 UD) with wide lanes effectively 3.5 meters per strip, making been gained capacity roads as much as 5809,2 smp/hour on both segments with the DS value i.e 0.71 on segment 1 and 0,70 on segment 2. Key words: Road Performance, Degrees of Saturation, Level of Service.